THE EFFECT OF PRUNING ON PHENOLOGICAL DEVELOPMENT AND FRUITING CAPACITY OF ALPHONSE LAVALLE TABLE GRAPE VARIETY IN THE MOSTAR AREA - Delić, Mersija; Behmen, Fikreta; Murtić, Senad; Sefo, Semira; Matijašević, Saša (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
During the three-year study of the influence of pruning on the phenological development and yield of the Alphonse Lavalle variety in the Mostar area, three pruning variants (28, 30 and 40 buds / vines) were applied in four replications. The phenological development of the variety took place within the limits of the average and in accordance with the temperature conditions. The total number of developed shoots and the number of bearing shoots was the highest in 2013 (total 21.72, birth rate 21.25), and the lowest in 2012 (total 18.67, birth rate 18.56). The highest yield of grapes per vine was recorded in 2013 (17.73 kg), and the lowest in 2011 (9.01 kg). The number of bunches per vine was the highest in 2013 (33.94), and the lowest in 2011 (26.71). Pruning variant III had the largest number of total (21.79) and native (21.64) shoots, and variant I the smallest (total 18.46, native 18.17). The highest yield of grapes per vine was recorded in variant II (14.47 kg), and the lowest in variant I (12.05 kg), while the number of bunches per vine was uniform in variants II (31.37) and III (31, 51).